Travelling wave and optical soliton solutions of the Wick-type stochastic NLSE with conformable derivatives. (July 2021) - Ulutas, Esma
Highlights: Wick-type stochastic Nonlinear Schrödinger equation with conformable derivatives and Kerr law nonlinearity is considered. The extended G'/G-expansion method and Jacobi elliptic function ansatz method are used. Travelling wave solutions, Jacobi elliptic function solutions, bright, dark and singular optical soliton solutions are obtained. Stochastic travelling wave solutions and stochastic optical soliton solutions are obtained. It is demonstrated how the obtained stochastic solutions are presented as Brownian motion functions solutions. Abstract: In this study, we have considered Wick-type stochastic nonlinear Schrödinger equation with conformable derivatives in Kerr law media. We have constructed exact various solutions of this equation using two analytic methods, white noise analysis and Hermit transform. We have applied the inverse Hermit transform to obtain stochastic solutions and then we have shown how these stochastic solutions can be presented as Brownian motion functional solutions by two application examples.